Effects of preharvest applications of calcium lactate and calcium chloride on the growth, yield and postharvest quality of sunflower microgreens - เขื่อนวัง, เปรมหทัย; คำสมุทร, Yodsawat; Pimtayan, Wisuda; Khitka, Boomrum; Pithakpol, Wasna (Health Science, Science and Technology Reviews, 2025)
The objective of this research was to study the effects of pre-harvest spraying of calcium on the growth, yield, and postharvest quality of sunflower microgreens. The experiment was designed using a Factorial in Completely Randomized Design with two factors: 1) Two types of calcium (calcium lactate and calcium chloride, CaCl2) and 2) Five levels of calcium concentration (0, 0.04, 0.4, 0.8, and 1.6%). Calcium solutions were daily sprayed to sunflower microgreens during 4-6 days after seed sowing and microgreens were harvested at 7th days, packed in plastic tray and stored at low temperature (10±2°C 80±2%RH) for 24 days. Results indicated that type of calcium had no significant effect on plant height, shoot weight, root length, or leaf length. However, it significantly affected on yield that spraying with calcium lactate solution causes sunflower microgreens to have higher yield than CaCl2 spraying. Regarding calcium concentration, the 0.04 and 0.4% resulted in higher yield than the other levels. As for the postharvest quality during 24 days at low temperature storage, calcium spraying has been shown to slow down weight loss and maintain quality. Sunflower microgreens sprayed with calcium lactate solution have a lower weight loss than CaCl2 solution, and in addition, calcium solution at 0.40 and 0.04% reduce weight loss, slow down leaf color change, and reduces bruising and decay of leaves and has better overall quality than other treatments, When considering interaction between calcium type and concentration levels, it was found that calcium lactate at 0.04 and 0.4% had higher yield and lower weight loss than the other treatments, as well as the lower production costs and higher profit than the other treatments.